Eksplorasi Pesan Dakwah pada Lagu Populer Alamate Anak Sholeh - Ni'amah, Luthfi Ulfa; Cahyono, Muchamad Rudi; Rafsanjani, M Habib Akbar (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
Da'wah using the medium of songs is being loved among society, especially among young people. None other than the supporting factors of technology and the reach of access in the digital world are increasingly massive. The song entitled